Calpastatin Overexpression Preserves Cognitive Function Following Seizures, While Maintaining Post-Injury Neurogenesis - Machado, Vanessa M.; Lourenço, Ana Sofia; Florindo, Cláudia; Fernandes, Raquel; Carvalho, Caetana M.; Araújo, Inês M. (Frontiers in Molecular Neuroscience, 2017)
In the adult mammalian brain, new neurons continue to be produced throughout life, in two main regions in the brain, the subgranular zone in the hippocampus and the subventricular zone in the walls of the lateral ventricles. Neural stem cells proliferate in these niches, and migrate as neuroblasts, to further differentiate in locations where new neurons are needed, either in normal or pathological conditions. However, the endogenous attempt of brain repair is not very efficient. Calpains are proteases known to be involved in neuronal damage and in cell proliferation, migration and differentiation of several cell types, though their effects on neurogenesis are not well known. Previous work by our group has shown that the absence of calpastatin, the endogenous inhibitor of calpains, impairs early stages of neurogenesis. Since the hippocampus is highly associated with learning and memory, we aimed to evaluate whether calpain inhibition would help improve cognitive recovery after lesion and efficiency of post-injury neurogenesis in this region. For that purpose, we used the kainic acid model of seizure-induced hippocampal lesion and mice overexpressing calpastatin. Selected cognitive tests were performed on the 3rd and 8th week after kainic acid-induced lesion, and cell proliferation, migration and differentiation in the dentate gyrus of the hippocampus of adult mice were analyzed using specific markers. Cognitive recovery was evaluated by testing the animals for recognition, spatial and associative learning and memory. Cognitive function was preserved by calpastatin overexpression following seizures, while modulation of post-injury neurogenesis was similar to wild type mice. Calpain inhibition could still be potentially able to prevent the impairment in the formation of new neurons, given that the levels of calpain activity could be reduced under a certain threshold and other harmful effects from the pathological environment could also be controlled.